2022
DOI: 10.3389/fendo.2022.942412
|View full text |Cite
|
Sign up to set email alerts
|

Serum iron is closely associated with metabolic dysfunction-associated fatty liver disease in type 2 diabetes: A real-world study

Abstract: AimsThere is still a debate about the relationship between serum iron and metabolic dysfunction-associated fatty liver disease (MAFLD). Furthermore, few relevant studies were conducted in type 2 diabetes mellitus (T2DM). Therefore, this study aimed to explore the association of serum iron levels with MAFLD in Chinese patients with T2DM.MethodsThis cross-sectional, real-world study consisted of 1,467 Chinese T2DM patients. MAFLD was diagnosed by abdominal ultrasonography. Based on serum iron quartiles, the pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 52 publications
3
3
0
1
Order By: Relevance
“…Notably, a meta-analysis demonstrated that MAFLD was more prevalent in T2DM patients (51.83%) than in non-diabetics (30.76%) ( 7 ). In the present real-world study, the prevalence of MAFLD in T2DM inpatients was 41.0%, which was close to the recent findings reported by our team (41.2%) ( 23 ).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Notably, a meta-analysis demonstrated that MAFLD was more prevalent in T2DM patients (51.83%) than in non-diabetics (30.76%) ( 7 ). In the present real-world study, the prevalence of MAFLD in T2DM inpatients was 41.0%, which was close to the recent findings reported by our team (41.2%) ( 23 ).…”
Section: Discussionsupporting
confidence: 91%
“…All T2DM subjects were diagnosed based on the WHO diagnostic criteria as our recent study ( 21 ). Based on the international expert consensus statement in 2020, the diagnosis of MAFLD in T2DM patients was consistent with our recent study ( 1 , 23 ). The definition of obesity, smoking status and alcohol use referred to our recent studies ( 19 , 20 ).…”
Section: Methodssupporting
confidence: 89%
“… 36 Likewise, the present study showed that the MAFLD prevalence in T2DM subjects was 49.5%, which was close to the prevalence (52.6%) of NAFLD reported in our previous study. 25 Like other studies including our recent studies, 24–26 , 33 , 37 , 38 the current study also showed negative correlations of the MAFLD prevalence with age and DD in T2DM patients. One possible explanation for this phenomenon was that early and young T2DM patients had a greater degree of hyperinsulinemia, which led to the uptake of free fatty acids in hepatocytes.…”
Section: Discussionsupporting
confidence: 85%
“…For detection of hepatic steatosis, abdominal ultrasound examination was conducted in each participant, which was in accordance with our previous reports. 26 , 32 Based on our recent study, 33 since all participants in the current study had T2DM, subjects with the evidence of liver steatosis on abdominal ultrasonography were diagnosed as MAFLD according to the definition of MAFLD. 9 …”
Section: Methodsmentioning
confidence: 99%
“…IO status in the liver can lead to many diseases [ 10 ], such as non-alcohol fatty liver disease and liver insulin resistance. Previous epidemiological studies reported that IO increases the risk of insulin resistance, indicating the linkage between IO and diabetes [ 11 ]. Although previous studies confirmed that IO is a risk factor for diabetes, the associated pathological mechanism is not clear.…”
Section: Introductionmentioning
confidence: 99%